Learning profiles and their relation to the experiences of learning generic skills at the end of the first year of university study - Hyytinen, Heidi; Tuononen, Tarja; Haarala-Muhonen, Anne (Frontiers in Education, 2024)
University students' approaches to learning and generic skills have important consequences for studying and success in higher education. However, person-oriented research, which explores how students with different learning profiles evaluate their learning of individual generic skills, has not been the core interest of previous studies. This study investigates the learning profiles of university students (N = 901) in two disciplines and their relations to the experiences of learning critical thinking, collaboration and communication at the end of the first study year. The interrelations of the variables were analysed with correlations and Latent Profile Analysis (LPA) estimating auxiliary variable relation. LPA yielded three learning profile groups that differed from each other in their approaches to learning: unreflective, dissonant and deep-organised, which respectively comprised 7%, 58% and 35% of the sample. The experiences of learning generic skills of the three learning profiles varied. The comparison of the profiles showed that students representing the deep-organised profile scored highest on all measured generic skills compared to the other two learning profiles.